Analisis Determinan Kinerja Keuangan Pada Lima Asset Perbankan Syariah Periode Tahun 2019-2022: Islamic Banking Financial Performance, ROA, CAR, EATAR, LDR, and NIM - Sarmadi, Ahmad; Widana, IGN Oka (Politeknik Ganesha Medan, 2024)
This research aims to analyze the determinants of financial performance in the five largest assets of Islamic banks during the period of 2019-2022. The research method used is quantitative research with a secondary data approach. The data used is obtained from the financial reports of the top five Islamic banks in Indonesia. The analysis technique employed in this study is panel regression analysis using SPSS 27 for multivariate analysis. The findings of the research indicate that the Earning Asset to Asset Ratio (EATAR) has a significant and very weak impact on Return On Asset (ROA), with an impact of 0.0196%. This suggests that the management of EATAR needs to be considered, even though its impact on ROA is relatively low. Similarly, the Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) also have a significant and weak influence on ROA, with impacts of 4.12% and 1.18% respectively. Furthermore, EATAR, LDR, and NIM have a significant and very weak effect on the Capital Adequacy Ratio (CAR), with impacts of 0.17%, 0.38%, and 0.47% respectively. However, when considered simultaneously, these three variables do not have a negative and significant influence on both ROA and CAR in the five Islamic banks in Indonesia. The combined effect of the three variables on ROA and CAR is relatively low, at 6.50% and 10% respectively. The predominant result of this research indicates that the Capital Adequacy Ratio (CAR) has a significant and sufficiently strong impact on Return On Asset (ROA), with an impact of 4.36%. This suggests that an adequate level of capital adequacy can contribute positively to the bank's profitability.